Mechanism of cognitive impairment after laparoscopic surgery and nursing application progress based on EEG monitoring - Xu, Juan; Lv, Xuejiao (Frontiers in Neurology, 2025)
As laparoscopic surgery becomes more complex, the early detection and management of postoperative neurological issues, particularly postoperative delirium and cognitive dysfunction, have gained prominence in clinical nursing. In recent years, electroencephalogram (EEG) monitoring has emerged as a non-invasive, real-time method for assessing brain function, and is increasingly being utilized in postoperative care. This includes evaluating the quality of anesthesia recovery, monitoring the balance of cerebral oxygen supply and demand, protecting neurological function, and overseeing postoperative sleep, demonstrating its potential benefits. This article provides a comprehensive review of the technical principles and application contexts of EEG monitoring in the nursing care of laparoscopic surgery patients, aiming to develop an optimized nursing model that encompasses the preoperative, intraoperative, and postoperative phases.